Tuberculosis and the Heart - José Patricio López‐López; Edith L. Posada‐Martínez; Clara Saldarriaga; Fernando Wyss; Carlos I. Ponte‐Negretti; Bryce Alexander; Andrés Felipe Miranda‐Arboleda; Manuel Martínez‐Sellés; Adrian Baranchuk (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Abstract Acquired tuberculosis continues to be a challenge worldwide. Although tuberculosis has been considered a global public health emergency, it remains poorly controlled in many countries. Despite being primarily a pulmonary disease, tuberculosis could involve the heart. This systematic review is part of the "Neglected Tropical Diseases and Other Infectious Diseases Involving the Heart" (the NET‐Heart Project) initiative from the Interamerican Society of Cardiology. This project aims to review the cardiovascular involvement of these heterogeneous diseases, advancing original algorithms to help healthcare providers diagnose and manage cardiovascular complications. In tuberculosis, pericardium involvement is relatively common, especially in AIDS, and tuberculosis is the most common cause of constrictive pericarditis in endemic countries. Myocarditis and aortitis by tuberculosis are rare. Clinical manifestations of cardiovascular involvement by tuberculosis differ from those typically found for bacteria or viruses. Prevailing systemic symptoms and the pericarditis diagnostic index should be taken into account. An echocardiogram is the first step for diagnosing cardiovascular involvement; however, several image modalities can be used, depending on the suspected site of infection. Adenosine deaminase levels, gamma interferon, or polymerase chain reaction testing could be used to confirm tuberculosis infection; each has a high diagnostic performance. Antituberculosis chemotherapy and corticosteroids are treatment mainstays that significantly reduce mortality, constriction, and hospitalizations, especially in patients with HIV. In conclusion, tuberculosis cardiac involvement is frequent and could lead to heart failure, constrictive pericarditis, or death. Early detection of complications should be a cornerstone of overall management.